Concurrent engineering: basis and implementation. (4th October 2004) - Bowonder, B.; Sharma, K.J.
Managing product development cycle time has been one of the critical competencies needed for meeting the competition. Using a series of approaches the product development process has been made concurrent. Overlapping phases of development involves intense interactions among team members, cross-functional teaming, use of information technology enablers and frequent reviews among team members, customers and suppliers. Taking up product development along with manufacturing process specifications improves manufacturability as well as assemblability. Many firms, including automobile firms and aerospace manufacturers have been able to reduce the product development cycle time along with the reduction in failure rates and rework. Enhancing horizontal interactions and early specification of deliverables facilitates coordination, paving the way for reducing time to market and product costs.